2014
DOI: 10.1159/000360608
|View full text |Cite
|
Sign up to set email alerts
|

Priapism in Homozygous Sickle Cell Patients: Important Clinical and Laboratory Associations

Abstract: Objective: To evaluate the relationship between the occurrence of priapism and important steady-state clinical and laboratory parameters in homozygous sickle cell disease (SCD). Subjects and Methods: Steady-state clinical and laboratory data were obtained from the medical records of 126 male patients seen in the clinic over a 7-year period. Estimated prevalence rates, correlation coefficients and independent t tests were calculated to assess the relationship between priapism and several important clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
4
20
2
Order By: Relevance
“…In men with SCD, vaso-occlusion and recurrent testicular infarction may contribute to hypogonadism [122,123]. Erectile dysfunction has been reported in as many as 21% to 35% and is likely a sequela of recurrent episodes of priapism [124,125]. Osegbe et al demonstrated that adult males with SCD, not taking hydroxyurea, have lower sperm count, motility and The participants assigned to hydroxyurea treatment had lower annual rates of crises than the participants given placebo (median, 2.5 vs. 4.5 crises per year, P < 0.001).…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
“…In men with SCD, vaso-occlusion and recurrent testicular infarction may contribute to hypogonadism [122,123]. Erectile dysfunction has been reported in as many as 21% to 35% and is likely a sequela of recurrent episodes of priapism [124,125]. Osegbe et al demonstrated that adult males with SCD, not taking hydroxyurea, have lower sperm count, motility and The participants assigned to hydroxyurea treatment had lower annual rates of crises than the participants given placebo (median, 2.5 vs. 4.5 crises per year, P < 0.001).…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
“…[18][19][20] The etiology of ED is unclear, but is largely the result of prolonged or recurrent priapism. Management of ED due to priapism depends on the extent of penile tissue fibrosis.…”
Section: Edmentioning
confidence: 99%
“…39,51 Although the long-term prognosis of children with initially less severe SCD may be better (especially in the future with continued improvements in supportive care), an individual patient's disease course is likely to involve significant problems. The specific risk of infertility secondary to HSCT also has to be balanced with the risk of reproductive problems related to SCD complications (impotence from priapism for men, [52][53][54] increased pregnancy complications for women [55][56][57] ) and also weighed against hydroxyurea therapy toxicity. 44,58,59 Thus, given the serious problems caused by SCD, some have questioned: Is the medical community actually harming patients with SCD by not offering them a curative therapy (HSCT) early and forcing these patients to live with a disease that causes high morbidity and premature mortality?…”
Section: Is There Clinical Equipoise?mentioning
confidence: 99%